The - editors Vincent B. Leitch... (Norton, 2001)
Edited by scholars and teachers whose interests range from the history of poetics to postmodernism, from classical rhetoric to ériture féminine, and from the social construction of gender to the machinery of academic superstardom, The Norton Anthology of Theory and Criticism promises to become the standard anthology in its field